Effects of Material Incentives and Non Material on Employee Satisfaction Employees - Muhammad Azhar Mushlihin (Tasharruf: Journal Economics and Business of Islam, 2019)
AbstractThe purpose of this study was to determine the effect of material and non-material incentives on employee job satisfaction at PT. Bank Tabungan Negara (Persero) Tbk. Makassar Branch.               The analysis method used to determine the effect of material and non-material incentives on employee job satisfaction is to use multiple linear regression analysis through the SPSS version 24.0 program.               Partially and simultaneously shows that the variables of material and non-material incentives can affect employee job satisfaction. These results imply that the company is able to create added value in the provision of additional wages which can ultimately increase the job satisfaction of its employees.Keywords: Material Incentives, Non Material Incentives, Employee Satisfaction.